Sosialisasi dan Pelatihan Pengolahan Kacang Tunggak dan Daun Kelor Menjadi Produk Pangan Fungsional di Desa Aik Berik Lombok Tengah - Nur Indah Julisaniah; Kurniasih Sukenti; Sukiman Sukiman; Evy Aryanti; Nurrijawati Nurrijawati; Baiq Jelita Puspita Sari (Sinergi dan Harmoni Masyarakat MIPA, 2026)
Cowpeas and moringa are agricultural products from the Fabaceae family that have great potential as functional food ingredients because they are rich in protein, fiber, vitamins, minerals, and bioactive compounds. Both plants have significant health benefits when processed properly. This community service activity teaches how to process cowpea seeds and moringa leaves into functional food products with high nutritional value and added economic value. The target participants for this activity are women and girls in Aik Berik Village who are members of the Benang Setokel Joint Business Group. The benefits for participants include increased knowledge and skills in producing functional foods from cowpea seeds and moringa leaves, which are easily found around their homes.